Associations between DAPT score and long-term mortality post PCI. (3rd October 2022) - Tan, M; Dinh, D; Gayed, D; Liang, D; Brennan, A; Duffy, S; Clark, D; Ajani, A; Oqueli, E; Roberts, L; Reid, C; Freeman, M; et al.
Abstract: Introduction: The dual antiplatelet therapy (DAPT) score was developed to identify patients more likely to derive benefit (score ≥2) or harm (score <2) from DAPT beyond 1-year post PCI. There is no study which looked at the DAPT score and long term outcomes post PCI in Australia. Purpose: We sought to examine long-term mortality after PCI by the DAPT score in patients treated with DAPT per local guidelines. Methods: We examined data from the MIG PCI database from 2005 to 2018 in whom the DAPT score could be derived and grouped them as score ≥2 or <2. Long-term mortality was assessed from National Death Index linkage. The primary endpoint was long-term mortality examined using survival analysis. Secondary endpoints included 30-day ischaemic outcomes and in-hospital major bleeding. Results: Out of 27, 740 patients in the study, 9, 401 (33.9%) had DAPT score ≥2. They were younger and included more females and higher prevalence of renal impairment. DAPT score ≥2 patients had higher in-hospital major bleeding, 30-day mortality, MI and target vessel revascularisation. DAPT score ≥2 patients had lower long-term survival to 12 years (p<0.001 for all). Conclusion: A third of all-comer PCI patients had DAPT score ≥2 with greater short-term risk of ischaemic and bleeding outcomes, as well as long-term mortality. Theoretically, those with DAPT score ≥2 would benefit from longer duration of DAPT as ischaemic risk outweighs bleeding risk. However, given our finding of increased short-term bleeding risk and long-term mortality, dynamic bleeding risk assessment should be undertaken to guide pharmacotherapy strategies. Funding Acknowledgement: Type of funding sources: None.